EVOLUTION OF CLINICAL MANIFESTATIONS OF WHOOPING COUGH IN CHILDREN IN THE POST-COVID-19 PANDEMIC PERIOD - Hladchenko, O.I.; Dybas, I.V.; Nadraga, A.B. (World of Medicine and Biology, 2025)
In recent years, an increase in the number of cases of pertussis has been recorded in Europe and Ukraine. The purpose of the study was to find out the features of pertussis in children in the first three years of life after the COVID-19 pandemic and compare them with clinical and laboratory data of similar patients who had pertussis before the pandemic COVID-19. A retrospective analysis of 97 patient charts of inpatients aged 0-36 months diagnosed with pertussis who were treated in the Lviv Regional Clinical Infectious Diseases Hospital in 2017–2019 and 2023–2024 was conducted. It was found that the course of the disease in the post-epidemic cohort was milder, with a higher incidence of respiratory complications; a number of differences in clinical manifestations, complete blood counts in children of different age groups, and in the period before and after the SARS-CoV-2 pandemic were identified. After the end of the COVID-19 pandemic, the weakening of population immunity, genetic mutations of Bordetella pertussis and the possible impact of SARS-CoV-2 infection on the immune response contributed to an increase in children's susceptibility to pertussis and changes in clinical manifestations of the disease.
Keywords: pertussis; children; COVID-19; course of disease; immune response